EFFECT OF ASTAXANTHIN CONCENTRATION IN ARTIFICIAL FEED TO INCREASE COLOR OF TIGER BARB (Puntius tetrazona) - Novia, Solvi; M. Tang, Usman; Putra, Iskandar (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACTThis research was conducted in April until May 2018, at the Laboratory of Aquaculture Technology, Faculty of Fisheries and Marine, University of Riau. The study aims of to influence the addition of astaxanthin in artificial feed to increase the color quality of Tiger Barb (Puntius tetrazona) and get the best dose of astaxanthin. This study uses an experimental method with a completely randomized design (CRD) of one factor with 4 treatment levels and 3 replications. The dose of astaxanthin in the treatment were: 0% astaxanthin, 1% astaxanthin, 3% astaxanthin, 5% astaxanthin. The size of fish was used is 3-5 cm with 10 stocking densities per aquarium. Maintenance lasts for 30 days and feed is given as much as 3% of the weight of biomass, the frequency of feeding is 3 times a day. Parameters observed included fish color, absolute length growth and absolute weight, survival rate and water quality. The results showed that the administration of astaxanthin had a significant effect on changes in the quality of the color of the Tiger Barb. The best treatment was at a dose of 5% which improved the quality of chest color 12.77, body 9.16, tail 14.00. The best absolute length growth is 0.55 cm, absolute weight is 0.47 grams and fish life is 100%. Keywords: Astaxanthin; Color; Tiger Barb; Puntius tetrazona